2017
DOI: 10.1002/adfm.201703523
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Neural Interfaces for Closed‐Loop Control of Neural Activity

Abstract: Microfabrication and nanotechnology have significantly expanded the technological capabilities for monitoring and modulating neural activity with the goal of studying the nervous system and managing neurological disorders. This feature article initially provides a tutoriallike review of the prominent technologies for enabling this two-way communication with the nervous system via electrical, chemical, and optical means. Following this overview, the article discusses emerging high-throughput methods for identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 329 publications
(571 reference statements)
0
22
0
Order By: Relevance
“…Taken together, we expect the platform to create new opportunities for multifunctional biointerfaces (e.g., neural electrodes) that can deliver soluble factors (e.g., neuromodulators) at physiologically-relevant time scales and doses. [29] where a short time-lapse video (20 frames that lasted for 6 seconds) was recorded with an inverted fluorescence microscope. Each video sample was then uploaded to ImageJ [30] and the intensity of every frame inside the sample was extracted into a grey value with a timestamp.…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, we expect the platform to create new opportunities for multifunctional biointerfaces (e.g., neural electrodes) that can deliver soluble factors (e.g., neuromodulators) at physiologically-relevant time scales and doses. [29] where a short time-lapse video (20 frames that lasted for 6 seconds) was recorded with an inverted fluorescence microscope. Each video sample was then uploaded to ImageJ [30] and the intensity of every frame inside the sample was extracted into a grey value with a timestamp.…”
Section: Resultsmentioning
confidence: 99%
“…On the application side, applying engineering practices such as closed‐loop control of neural implants may improve clinical outcomes by better controlling the stimulation inputs. Multimodal electrical and optical interfaces are well‐placed to support this capability as they allow a reduction in stimulating artifacts on the recorded signal . Closed‐loop control is of interest in applications such as epileptic seizure prevention, where algorithms for electrical detection and optogenetic interruption of seizures in real‐time have been demonstrated, and in visual prostheses, where the simulated stimulation level can be adjusted dynamically on‐line based on the response of retinal neurons .…”
Section: Emerging Technologies and Challengesmentioning
confidence: 99%
“…Rivnay et al present a broader review of materials for electrical, optical, magnetic and mechanical (ultrasound) based modalities of nerve stimulation, whereas ref. provides a very broad review of electrical, optical and chemical monitoring of biological activity, and how that can be used for closed‐loop control of neural processes. In contrast, the review presented here covers the full range of optical interfaces, including optogenetics, infrared neural stimulation, nanoparticle‐enhanced optical stimulation, and photochemical tools with the focus on biological considerations for optical implants.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that similar benefits are observed due to therapeutic insoluble factors, such as topographical cues (e.g., varied surface roughness) and presentation of immobilized biomolecules. 31 NPG has significant potential to serve as a multifunctional device coating, building on several attributes already discussed and some to be introduced in this section. We specifically focus on NPG as a neural interface for monitoring and modulating neural tissue behavior, which is a promising tool for neuroscience as well as a device for treatment of neurological disorders.…”
Section: Multifunctional Biomedical Device Coatingsmentioning
confidence: 99%